Looking through cinema: Representation of racial identity development in Amma Asante’s Belle movie (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2022)
This research studied the concept of racial identity development of the main character in Amma Asante’s movie Belle. This research also describes the social relations between the main character’s identity development and women’s agency. The analysis is founded on the theory of racial identity development and the sociology of literature. The results showed that, in Belle movie, the main character experiences all the rounds of racial identity development which challenges her agency to make the social change she wanted. Thus, these two subtopics correlated with each other that also represented how the racial identity development and the women’s agency influence the socio-cultural life of the main character in understanding her existence among other beings.